(untitled) (Research, Society and Development, 2019)
Water is a precious substance, limited and indispensable to life, presently many preservation campaigns grow in the world. In response to this, several proposals for the use of water as a solution to mitigate the impacts caused by water reserves, a technique that is growing are those of rainwater collected by the coverages, which, in addition to decreasing floods, reduces their scarcity and preserves the water reserves. The objective of this study is to study the economics obtained through the use of rainwater in order to achieve a reduction in the use of drinking water in the Unipac-Faculdade Presidente Antônio Carlos de Teófilo Otoni School. data collection in the UNIPAC / Teófilo Otoni, where it was possible to obtain data of accounts present in the invoices, pluviometric data, coverage areas, types of sanitary appliances and the population that frequents the university, with these data it was possible to calculate the actual consumption of monthly water and estimates. Based on the data obtained by the users through interviews it was possible to perform the average frequency and time of use of the existing apparatuses in the university. After comparing the estimated water volume with the average made with the sanitation company’s invoices (COPASA), a difference can be verified between the estimated consumption of the real, in this way there was a need for corrections of the values. Corrections were made on all appliances, and so it was possible to obtain the amount of rainwater that could be used. The rainwater harvesting method at UNIPAC / Teófilo Otoni proved to be a viable system generating a significant reduction of treated water.